ANALISIS PERILAKU MENYIMPANG PADA SISWA YANG KECANDUAN BERMAIN GAME ONLINE DI SMPN 01 SEBAWI KABUPATEN SAMBAS - Mira Azrina; Fatmawati Fatmawati; Imran Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe title of this thesis is "The Analysis of Abberant Behavior to the Students Who Addicted to Playing Online Games in SMPN 01 Sebawi Sambas Regency". The general problem in this study is how the abberant behavior to the students who addicted to playing online games at SMPN 01 Sebawi, Sambas Regency?. The purpose of this study was to determine the forms of abberant behavior in students who are addicted to playing online games and deviant behavior factors of students who are addicted to playing online games. The writer used is qualitative approach and descriptive methods. Data collection techniques used were observation, interviews, and documentation. This study analysis is writer in descriptive which use 7 informants who consisting of social studies teachers of class VII C and VIII A, parents of one of the informants who stole, a cafe keeper, and three students who have abberant behavior due to addiction to playing games online. The results of this study show that students who addicted to playing online games do the abberant action a nonconform abberant behavior namely insulting, fighting, skipping school and lying. Beside there is informants do the abberant behavior that is antisocial namely introverted behavior (closed). In addition, one of the student informants who addicted to playing online games also stole his father's savings to buy diamond games online. As the result the factors that influence the students who addicted to playing online games such are the factor lack of control from parents and the second is a peer factor.Keywords: Abberant Behavior, Addicted to Playing Online Games, Students.